2009
DOI: 10.1111/j.1548-1492.2009.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a Hurdler: How Learning Settings Afford Identities

Abstract: In this article, we present a model for thinking about how learning settings provide resources for the development of the practice-linked identities of participants, drawing on data from a study on an African American high school track and field team. What does it mean to make an identity available in the context of a learning setting? In this article, we draw on current theories in anthropology, psychology, sociology, and sociocultural theory to develop a conceptual frame that might be helpful in addressing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
99
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(126 citation statements)
references
References 28 publications
1
99
0
2
Order By: Relevance
“…Nasir and Cooks (2009) suggested that Wenger "reconceptualizes learning from an in-the-head phenomenon to a matter of engagement, participation, and membership in a community of practice" (p. 42). The modes of belonging indicate how people position themselves in relationship to communities of practice, and thus the forms of becoming that are possible.…”
Section: Modes Of Belongingmentioning
confidence: 99%
“…Nasir and Cooks (2009) suggested that Wenger "reconceptualizes learning from an in-the-head phenomenon to a matter of engagement, participation, and membership in a community of practice" (p. 42). The modes of belonging indicate how people position themselves in relationship to communities of practice, and thus the forms of becoming that are possible.…”
Section: Modes Of Belongingmentioning
confidence: 99%
“…This students' response was to assuage the stereotype threat by becoming an active participant in class by purposefully, and even defiantly, proving tacit beliefs wrong. In this case, mitigating stereotype threat required conscious agency and self-efficacy: "Within these figured worlds, identity is constructed as individuals both act with agency in authoring themselves and are acted upon by social others as they are positioned (as members, nonmembers, or certain kinds of members" (Nasir & Cooks, 2009). Authoring his own identity as a Black male athlete, this participant actively creates conditions for positive perceptions.…”
Section: Some People Are Afraid Of Us For [Pause] I Don't Know They mentioning
confidence: 99%
“…Case study data of secondary schools with high percentages of collegeattending graduates (Lewis-Charp & Law, 2014), insights from students reporting satisfaction and engagement with their schooling experiences (Antrop-González & DeJesús, 2006;LewisCharp & Law, 2014) and studies conducted in out of school contexts provide additional evidence that African American students willingly assume apprentice, or learner, roles in settings in which it feels accessible and worthwhile to do so (Nasir & Cooks, 2009;. Within and outside of the classroom, relevant experiences assist students in assuming identities and behaviors that are congruent with learning content, skills and essential understandings of a discipline.…”
mentioning
confidence: 99%
“…In addition to potentially influencing student performance and mental productivity, the way teachers see students within their classrooms and the relationships they have with them can also affect the resources available to students as they continue to carve out a sense of self (Nasir & Cooks, 2009). Case study data of secondary schools with high percentages of collegeattending graduates (Lewis-Charp & Law, 2014), insights from students reporting satisfaction and engagement with their schooling experiences (Antrop-González & DeJesús, 2006;LewisCharp & Law, 2014) and studies conducted in out of school contexts provide additional evidence that African American students willingly assume apprentice, or learner, roles in settings in which it feels accessible and worthwhile to do so (Nasir & Cooks, 2009;.…”
mentioning
confidence: 99%
See 1 more Smart Citation